MODELO DE ESTIMATIVA DA RADIAÇÃO LÍQUIDA E SUA APLICAÇÃO NA DETERMINAÇÃO DA EVAPOTRANSPIRAÇÃO POTENCIAL - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
This study aimed to assess and develop a physical mathematical model to estimats the net radiation. For this we used weather data collected from the meteorological station of the Department of Physics and Meteorology of the Escola Superior de Agricultura "Luis de Queiroz" - ESALQ - University of São Paulo - USP, Piracicaba, Brazil, according to the global radiation (Qg) relative humidity (UR) and average daily temperature (T).The proposed methodology let us to determine the net radiation based on data more easily accessible and relevant to various daily human activities and therefore of great importance in engineering projects aimed at harnessing solar energy in its many forms. The performance of the model estimate of net radiation and its application in determining the potential evapotranspiration was verified by analyzing the coefficients of determination (R2) and agreement index of Willmott (d) applied to the observed and estimated data. The values estimated by the proposed method were compared with values measured by a net radiometer and the results showed that the proposed methodology was efficient for the estimation of net radiation with speed and simplicity. The data set was subjected to a simple linear regression analysis, obtaining a good adjustment between measured and estimated values. The use of estimated net radiation was efficient in the estimation of evapotranspiration by the methods of Penman Monteith, Priestley Taylor adjusted and Penman modified by the proposed model with a good adjustment when compared with the values measured for a period of 89 days, with determination coefficient (R2) ranging from 0.910 to 0.940. The proposed methodology is applicable when the meteorological variables needed to estimate potential evapotranspiration when not always are available, particularly those related to the solution of the aerodynamic term (wind velocity and vapor pressure deficit in the air), thus the methods are important to estimate the ETo based on climatic elements that can be obtained in a practice way. The satisfactory correlation found with the net radiometer makes the method of potential use in the region under study because the knowledge of evapotranspiration or latent heat flux contributes to a more rational use of water in crops in critical stages of growth and reproductive when water is a limited factors. Thus, for the climate of the town looked, it was possible to estimate with good precision the value of the net radiation, based on the theory proposed generating equivalent values those obtained by classical methodology for Piracicaba, SP.
Keywords: balanço global de radiação; Razão de Bowen; radiação global; net radiation balance; ratio Bowen; global radiation; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA